Sense of Place pada Kawasan Masjid Tua di Pekojan Jakarta untuk Landasan Revitalisasi Kawasan - Sugeng Eko Prasetyo; Sisil Friedlyka Amanda Puspitasari Sahono; Yehezkiel Leonard Purba; Yostan Putra Halawa (Jurnal Arsitektur Wastu Padma, 2023)
The Pekojan area is a residence that has historic old mosques in Jakarta which are still used by the community every day. This condition causes this environment to actually have the potential to become a religious tourism area and an object that forms the character of a leading historical city area in Jakarta. This research focuses on the area's sense of place as an important element in carrying out revitalization to improve the character and quality of the area. The method used is a qualitative method with data collection techniques in the form of observations and interviews. The results of the research show that in order to strengthen the character and sense of place of the area, it is necessary to: (1) Strengthen urban design elements to support increasing the area's sense of place such as signage, construction of pedestrian paths, availability of parking and good environmental circulation, (2) Participation-based programs community to act as a form of informal supporting activity such as managing mosques, social and economic activities that support tourism activities.